Implementasi Gerakan Literasi Sekolah dalam Meningkatkan Kemampuan Membaca Siswa Kelas IV SDN 07 Sebalo - Sani, Selpiana; Silvester, Silvester (STKIP HARAPAN BIMA, 2025)
Reading ability is a basic foundation in the learning process. However, students' reading interest is often low. The purpose of this study was to describe the implementation of the School Literacy Movement (GLS) in improving the reading ability of fourth-grade students at SDN 07 Sebalo. GLS is a program initiated by the Ministry of Education and Culture to foster a culture of literacy in elementary schools. This study uses a qualitative approach with a descriptive method. Data collection techniques include observation, interviews with class teachers, and documentation studies related to literacy activities in schools. This study will analyze the impact of literacy activities on improving students' reading ability. The results of the study showed that the implementation of GLS at SDN 07 Sebalo was carried out through three main stages, namely reading habits for 15 minutes before the lesson began, developing reading activities through reading corners in the classroom, and literacy activities integrated into learning. The results of this study are expected to provide recommendations for other schools to improve students' reading interest and ability.